The Milan system for reporting salivary gland cytology: A retrospective analysis of 1384 cases in a tertiary Southeast Asian institution. Issue 5 (5th February 2020) - Lee, Jaslyn Jie Lin; Tan, Hui Min; Chua, Darren Yee Shuen; Chung, Jocelycn Gaik Kooi; Nga, Min En
Abstract : Background: The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) aims to provide a common language for risk stratification and management. We examine the incidence of MSRSGC categories and the corresponding risk of malignancy (ROM) within a tertiary referral centre in Southeast Asia. Methods: Salivary gland fine needle aspirations (FNAs) performed within a 10‐year period were classified retrospectively according to the MSRSGC. Cytohistologic correlation was performed. The results were compared with the existing literature, including Asian and Western studies. Results: A total of 1384 salivary gland FNAs were evaluated, 421 with corresponding histology. The category distribution was: nondiagnostic, 28.9%; nonneoplastic, 18.0%; atypia of undetermined significance (AUS), 9.8%; benign neoplasm, 32.9%; salivary gland neoplasm of uncertain malignant potential (SUMP), 5.7%; suspicious for malignancy, 1.6%; and malignant, 3.2%. The ROMs were: nondiagnostic, 10.0%; nonneoplastic, 17.5%; AUS, 29.5%; benign neoplasm, 0.5%; SUMP, 17.1%; suspicious for malignancy, 83.3%; and malignant, 100.0%. Our relatively high nondiagnostic rate likely reflects preanalytical factors, whereas our low malignancy rate may be related to population and health care accessibility. Our nonneoplastic ROM was 17.5% compared with 5% to 10% in the literature, likely due to the relatively small number of excised cases; the ROM for SUMP was 17.1% versus 21% to 44% in the literature, possibly reflecting a significant proportion of benign basaloid neoplasms on histology. Interestingly, all false‐negative cases in the nonneoplastic category were lymphoid‐rich lesions. Conclusion: This is one of the largest single‐institution studies in the existing literature documenting both the incidence and ROMs of MSRSGC categories. We also highlight specific challenges surrounding lymphoid‐rich lesions. Abstract : This article presents the incidence and corresponding risk of malignancy of diagnostic categories in salivary gland fine needle aspirations, using The Milan System for Reporting Salivary Gland Cytopathology, within a tertiary referral center in Southeast Asia. The data are compared with the current literature, with a discussion of differences as well as challenges in reporting fine needle aspirations of salivary gland lesions.